Implementasi Evaluasi Model Kirkpatrick Pada Pelatihan Bina Keluarga Balita Holistik Integratif dan Stunting - Findiastuti Rinaldy; Poppy Siska (Pancanaka, 2022)
Field workers have crucial roles for accelerating stunting reduction through optimizing BKB-HI, so field workers received training that is related to the substance BKB-HI and stunting prevention. Training is given through zoom meetings application and e-learning, It need to be evaluated for identifying effectiveness and sucessful of the training. This research using Kirkpatrick’s evaluation model with mix method. Quantitative data was strengthened by qualitative data, obtained from the results of indepth interview with six informants. Research focuses on evaluation level 1 (reaction), level 2 (learning) and level 3 (behavior). The evaluation of level reaction shows positive reaction to the training process with score of 4,7 or statisfy. At the learning level, the evaluation is based on the results of participant’s pre test and post test. The data obtained were analyzed by dependent T-Test and obtained p value = 0,000 (<0,05). It means there is significant difference between before and after the training, with increasing the average value of participants by 22,46. The evaluation of behavior level is carried out based on the follow up plan implementation by participants for 3 months after training, indicate 75% follow up plan has implemented. Most of the participants apply the substance obtaned from training.